Characterization of alkaline phosphatases activities in uterine secretion of buffaloes - GHOSH, JYOTIRMOY; ROY, SUDHIR C (The Indian Journal of Animal Sciences, 2014)
Alkaline phosphatases is reported as a predominant protein in buffalo uterine luminal secretion during the late- luteal phase of the cycle. Since the biochemical properties of this important protein are not known, an experiment was designed to purify and characterize the alkaline phosphatase from buffalo uterine secretion. The enzyme could be purified from uterine luminal fluid by 2 chromatography steps using DEAE cellulose ion-exchange and Sephacryl S-200 HR gel-filtration columns. The molecular weight of the purified protein was 179 kDa by non-reducing SDS- PAGE. Reduction by ß-metcaptoethanol yielded 136kDa and 43kDa bands indicated presence of 2 separable subunits of this protein. Complete inhibition of activity by ß-mercaptoethanol and partial inhibition by iodoacetamide indicated that both the subunits are essential for bioactivity. Three isoforms with pI values 5.9, 6.0 and 6.2 were detected by iso-electric focusing. Purified enzyme showed optimum activities at 37°C in pH ranges 10.5 to 11.0. It is a temperature sensitive enzyme as evidenced by a loss of 91% enzyme activity within 28 h of room temperature storage. The loss of activity was slow (12% per day) at 4p C storage indicating importance of cold chain maintenance while processing. The SDS proved to be a better detergent compared to Triton X100 as less inhibition (46% vs 76%) of enzyme activities was observed with the former. Inhibition of activities by metal chelators confirmed that it was metallo- phosphatase. Further study would help exploring its role in buffalo uterine microenvironment.